Jeunes diabétiques et projets d'orientation - Joëlle Mezza; Valérie Cohen-Scali; Corinne Lecomte; Nadia Lemasson; Chloé Stoïanoff-Nenoff
This exploratory research aims to understand the diabetic teen-agers' way of life, and the consequences of the day-to-day management of the illness on their career projects. In reference to Dumora's model about vocational dynamic (1990), we tried to identify the main psychosocial processes involved in the way these adolescents build their identity, related to career choices. We made two assumptions : first of all, teenagers with diabetes can develop skills, which are transferable to other fields. Secondly, teenagers with diabetes may integrate the disease contraints to make their career choices. Through the qualitative analysis of 11 semi- structured interviews, it seems that our population does not behave in a different way than other teenagers and does not incorporate the impact of their illness as a matter of priority in their future orientation.